Chondrocyte-Specific Knockout of TSC-1 Leads to Congenital Spinal Deformity in Mice. (24th April 2017) - Yang, Cheng; Chen, Yuhui; Li, Zhen; Cao, He; Chen, Keming; Lai, Pinglin; Yan, Bo; Huang, Bin; Tang, Jiajun; Fan, Shicai; Cai, Daozhang; Jin, Dadi; et al.
Abstract : Congenital spinal deformity is the most severe clinical orthopedic issue worldwide. Among all the pathological processes of congenital spinal deformity, the imbalance of endochondral ossification is considered to be the most important developmental cause of spinal dysplasia. We established chondrocyte-specific TSC-1 knockout (KO) mice to overactivate the energy metabolic component, mammalian target of rapamycin complex 1 (mTORC1), and measured the spinal development by general, imaging, histological, and Western-blot assessments. In addition to skeletal dysplasia, the KO mice displayed severe congenital spinal deformity and significant intervertebral disc changes. This study suggests that, in the process of endochondral ossification, excessive activation of mTORC1 signaling in chondrocytes induces obvious spinal deformity, and the chondrocytes may be the cell type responsible for congenital spinal deformity.